Seasonal Variations and Associated Factors of Gout Attacks: a Prospective Multicenter Study in Korea - Choi, Hyo Jin; Moon, Ki Won; Kim, Hyun-Ok; Lee, Yeon-Ah; Hong, Seung-Jae; Jung, Ju-Yang; Kim, Hyoun-Ah; Suh, Chang-Hee; Ha, You-Jung; Kim, In Je; Lee, Jisoo; Park, Eun-Kyoung; et al. (Journal of Korean medical science, 2020)
We purposed to evaluate the seasonality and associated factors of the incidence of gout attacks in Korea. We prospectively enrolled patients with gout attacks who were treated at nine rheumatology clinics between January 2015 and July 2018 and followed them for 1-year. Demographic data, clinical and laboratory features, and meteorological data including seasonality were collected. Two hundred-five patients (men, 94.1%) were enrolled. The proportion of patients with initial gout attacks was 46.8% (n = 96). The median age, body mass index, attack duration, and serum uric acid level at enrollment were 50.0 years, 25.4, 5.0 days, and 7.4 mg/dL, respectively. Gout attacks were most common during spring (43.4%, < 0.001) and in March (23.4%, < 0.001). A similar pattern of seasonality was observed in the group with initial gout attacks. Alcohol was the most common provoking factor (39.0%), particularly during summer (50.0%). The median diurnal temperature change on the day of the attack was highest in the spring (9.8°C), followed by winter (9.3°C), fall (8.6°C), and summer (7.1°C) ( = 0.027). The median change in humidity between the 2 consecutive days (the day before and the day of the attack) was significantly different among the seasons (3.0%, spring; 0.3%, summer; -0.9%, fall; -1.2%, winter; = 0.015). One hundred twenty-five (61%) patients completed 1-year follow-up (51% in the initial attack group). During the follow-up period, 64 gout flares developed (21 in the initial attack group). No significant seasonal variation in the follow-up flares was found. In this prospective study, the most common season and month of gout attacks in Korea are spring and March, respectively. Alcohol is the most common provoking factor, particularly during summer. Diurnal temperature changes on the day of the attack and humidity changes from the day before the attack to the day of the attack are associated with gout attack in our cohort.